Effect of High-Intensity Interval Training, Moderate Continuous Training, or Guideline-Based Physical Activity on Peak Oxygen Uptake and Myocardial Fibrosis in Patients With Myocardial Infarction: Protocol for a Randomized Controlled Trial - Shi, Xiaohe; Chen, Xianyuan; Qiu, Xinfan; Luo, Wei; Luo, Xinyi; Liu, Hui; Geng, Qingshan; Ma, Huan; Xue, Ling; Guo, Lan (Frontiers in Cardiovascular Medicine, 2022)
Introduction High-intensity interval training (HIIT) is an emerging method of cardiac rehabilitation, which is more and more popular in recent years. Research into the effect of HIIT on peak oxygen uptake (VO2 peak) and myocardial fibrosis among patients with myocardial infarction (MI) is lacking. Here, we describe the rationale along with the protocol for a clinical trial to test the following hypotheses: (1) compared with the control group, VO2 peak will be increased in both the moderate-intensity continuous training (MICT) and HIIT groups and (2) compared with the control group, myocardial fibrosis due to MI will be improved by HIIT and MICT. Methods and Analysis This is a single-center, randomized controlled clinical trial. In total, 180 patients with MI are to be recruited for this study. VO2 peak will be tested by cardiopulmonary exercise testing (CPET) and myocardial fibrosis will be evaluated by cardiac MR. A variety of blood and psychometric tests and also the peripheral arterial tonometry, reactive hyperemia index for microvascular endothelial function, and microvascular blockage or digital vasomotor response are included. Ethics and Dissemination The ethics committee of the Guangdong Provincial People's Hospital has authorized this mechanistic clinical research. Peer-reviewed articles and conference presentations will be used to disseminate the findings. Trial Registration Number NCT04863677.